2010
DOI: 10.1086/649899
|View full text |Cite
|
Sign up to set email alerts
|

HIV Infection and Aging Independently Affect Brain Function as Measured by Functional Magnetic Resonance Imaging

Abstract: We investigated interactions between HIV and aging on brain function demands using functional magnetic resonance imaging (fMRI). A multiple regression model studied the association and interaction between fMRI measures, HIV serostatus, and age for 26 HIV infected (HIV+) and 25 seronegative (HIV−) subjects. While HIV serostatus and age independently affected fMRI measures, no interaction occurred. Functional brain demands in HIV+ subjects were equivalent to ~15–20 year older HIV− subjects. Frailty parallels bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
94
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(111 citation statements)
references
References 15 publications
13
94
3
1
Order By: Relevance
“…In contrast to several recent reports, we did not observe hypo-activation in the primary visual regions of HIV-infected patients [17], [18]. Previous studies have shown decreased regional cerebral blood flow (CBF) in the primary visual cortices during rest, and reduced fMRI BOLD activation in occipital cortices during visual stimulation.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to several recent reports, we did not observe hypo-activation in the primary visual regions of HIV-infected patients [17], [18]. Previous studies have shown decreased regional cerebral blood flow (CBF) in the primary visual cortices during rest, and reduced fMRI BOLD activation in occipital cortices during visual stimulation.…”
Section: Discussioncontrasting
confidence: 99%
“…The current study did observe greater activation (marginal means) in the left occipital region in uninfected controls, but this effect did not approach significance. This difference between studies may reflect the substantially larger sample size used by Ances et al, as these studies had more than twice as many participants per group than the current study and thereby, greater sensitivity to detect smaller effects [17], [18]. However, Ances and colleagues also recently showed that the test-retest reliability of fMRI (BOLD and CBF) measures in HIV-infected patients are much lower than controls, and that the intrinsic coupling between oxygenation and blood flow is aberrant in HIV-infected patients [19].…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…3 individuals 15-20 years older (Ances et al, 2010). In an adult and older adult HIV+ cohort, Fazeli et al (2014) elucidated both the presence of subtle cognitive impairment in 47% of the study sample and the persistence of a mild and diffuse pattern of cognitive impairment in the era of HAART.…”
mentioning
confidence: 99%